Evaluation of Effectiveness of Vitamins C and E on Prevention of Renal Scar due to Pyelonephritis in Rat - Fatemeh Emamghorashi; Seyed Mohamad Owji; Mohammad Motamedifar (Advances in Urology)
Aim was evaluation of the effects of cosupplementation of, vitamins E and C, in preventing renal scarring in acute pyelonephritis. Animals and Treatments. Sixty rats were used, bacteria was injected through kidney. The rats were arranged randomly in 3 groups of 20 rats each. Rats in groups 1 and 2 were given once-daily intraperitoneal injections of gentamicin for ten consecutive days, beginning on the third day after inoculation. In group 2, vitamins E and C cotreatment and in group 3, vitamins E and C cotreatment without gentamicin injection were started. Three rats in each group were killed 24 hours after the inoculation (for infection and inflammation document) and forty-eight hours after the antibiotic injection (for efficacy of treatment). After eight weeks, the rest of rats were killed, and kidneys evaluated for percent of scaring. Result. There was also significant difference of degree of scar formation (1.4 and 3.4% versus 8.6%, 𝑃=.001). The group which received gentamicin only had moderate to severe scaring, but the two groups which received vitamin C and vitamin E showed no or mild renal scaring. Conclusion. The study showed that administration of antioxidants can protect scaring due to pyelonephritis with or without antibiotic administration.